Optimizing Natural and Cultural Potential for Green Tourism in Poso Regency - Abdi Sakti Walenta (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Poso Regency, Central Sulawesi, holds immense natural and cultural tourism potential, including megaliths, Lake Poso, and local traditions, yet faces challenges in effective promotion. Despite this potential, research on how green tourism marketing can address promotion gaps, sustainability issues, and competitiveness in Poso remains limited. This study aims to explore green tourism marketing strategies that optimize these assets to enhance destination competitiveness. Utilizing a qualitative library research approach, the study analyzes secondary data from journals, reports, and academic publications. Findings reveal that digital marketing through social media platforms significantly expands audience reach, effectively promoting Poso’s unique attractions. Community involvement in tourism management strengthens the local economy and preserves cultural heritage, fostering authentic tourist experiences. However, limited infrastructure, inadequate accessibility, and negative security perceptions hinder progress. The study concludes that integrating digital marketing, community participation, and sustainable practices is essential for Poso’s tourism development. Recommendations include enhancing digital promotion with engaging content, improving transportation and signage, and empowering local communities through training to manage tourism sustainably. These strategies can position Poso as a leading green tourism destination, supporting economic growth and cultural preservation.